Ø§ÙÙÙØ§ÙÙØ© Ø§ÙØ¹ØµØ§Ø¨ÙØ© ÙØ¹ÙØ§ÙØªÙØ§ Ø¨Ø§ÙØ§Ø³ØªÙØ±Ø§Ø± Ø§ÙÙÙØ³Ù ÙØ¯Ù Ø·ÙØ¨Ø© Ø§ÙØ¬Ø§ÙØ¹Ø© - Ø®ÙÙÙ Ø§ÙØ¹Ø¨ÙØ¯Ù, Ø§ÙØ¯ÙØªÙØ±Ø©: Ø¹ÙØ±Ø§Ø¡ Ø§Ø¨Ø±Ø§ÙÙ (Sciences de l'Homme et de la SociÃ©tÃ©, 2015)
ÙØ¯ÙØª Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø§ÙØØ§ÙÙØ© Ø¥ÙÙ Ø§ÙÙØ´Ù Ø¹Ù Ø·Ø¨ÙØ¹Ø© Ø§ÙØ¹ÙØ§ÙØ© Ø§ÙØ§Ø±ØªØ¨Ø§Ø·ÙØ© Ø¨ÙÙ Ø§ÙÙÙØ§ÙÙØ© Ø§ÙØ¹ØµØ§Ø¨ÙØ© ÙØ§ÙØ§Ø³ØªÙØ±Ø§Ø± Ø§ÙÙÙØ³ÙØ ÙØ¶ÙØ§Ù Ø¹Ù Ø§ÙØªØ¹Ø±Ù Ø¹ÙÙ Ø§ÙÙÙØ§ÙÙØ© ÙØ§ÙØ§Ø³ØªÙØ±Ø§Ø± Ø§ÙÙÙØ³Ù ÙØ¯Ù Ø§ÙØ¬ÙØ³ÙÙ ÙÙ Ø·ÙØ¨Ø© Ø§ÙØ¬Ø§ÙØ¹Ø©. ÙÙØ¯ ØªÙÙÙØª Ø¹ÙÙØ© Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ (370) Ø·Ø§ÙØ¨ÙØ§ ÙØ·Ø§ÙØ¨Ø©Ø ÙÙØ´ÙØª ÙØªØ§Ø¦Ø¬ Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¹Ù ÙØ¬ÙØ¯ Ø¹ÙØ§ÙØ© Ø§Ø±ØªØ¨Ø§Ø·ÙØ© Ø³Ø§ÙØ¨Ø© Ø¯Ø§ÙØ© Ø§ØØµØ§Ø¦ÙÙØ§ Ø¨ÙÙ Ø§ÙÙÙØ§ÙÙØ© Ø§ÙØ¹ØµØ§Ø¨ÙØ© ÙØ§ÙØ§Ø³ØªÙØ±Ø§Ø± Ø§ÙÙÙØ³ÙØ ÙØ¹Ø¯Ù ÙØ¬ÙØ¯ ÙØ±ÙÙ ÙÙ ÙØ³ØªÙÙ Ø§ÙÙÙØ§ÙÙØ© Ø¨ÙÙ Ø§ÙØ¥ÙØ§Ø« ÙØ§ÙØ°ÙÙØ±Ø ÙÙØ°ÙÙ Ø¨Ø§ÙÙØ³Ø¨Ø© ÙÙØ§Ø³ØªÙØ±Ø§Ø± Ø§ÙÙÙØ³ÙØ ÙÙØ¯ Ø®Ø±Ø¬Øª Ø§ÙØ¯Ø±Ø§Ø³Ø© Ø¨Ø¹Ø¯Ø¯ ÙÙ Ø§ÙÙÙØªØ±ØØ§Øª ÙØ§ÙØªÙØµÙØ§Øª. Â  AbstractÂ : Â Â Â Â Â Â Â Â Â Â  The present study aimed to reveal the nature of the correlation between neurotic perfectionism and psychological stability, as well as to identify the luxury psychological and stability in both sexes of university students. The study sample consisted of (370) students, revealed the results of the study on the presence of correlation is negative statistically significant between luxury neurotic and psychological stability, and the absence of differences in the luxury level between males and females, as well as for psychological stability, the study came up with a number of proposals and recommendations.